Necesidad de tratamiento psicológico en personas con riesgo de cáncer hereditario que inician consejo genético. Estudio de variables predictoras - Cruzado, Juan A.; Hernández, Vanesa; Pérez-segura, Pedro; Olivera, Helena; Sanz, Ruth; Suárez, Alejandra; Mendoza, Silvia (Psicooncología, 2005)
A study of Oncological Genetic Counseling (CGO) participants is realized, previously to begin the process, with the following aims: a) to provide descriptive data about cancer risk perception, Anxiety-Trait, coping competence, anxiety/depression, cancer-specific worries, previous psychological disorders, stressful life events during last 3 year, and sociodemographic and clinical characteristics, b) to determine if there are differences between 3 hereditary cancer risk syndromes: breast/ovarian, colon and others on those variables; c) to evaluate psychological intervention needs; d) to determine if those variables (risk perception, Anxiety-Trait, cancer previous, number of cancer relatives and stressful life events) can predict the need of psychological treatment. 155 participants were assessed on CGO Unit at Hospital Cl?nico San Carlos with hereditary risk of cancer (breast/ovarian: 77; colon: 53; others: 35). The sample characteristics were: 76.8% women, age mean: 44 years, 70% were married with children, and hight educational level (40% universitary studies). There were 37% with previous cancer diagnostic. Risk perception was moderately high: there were 34% that considered his/her risk higher than 50% and 20% considered that risk was higher than 75%. Most participants considered themselves with good ability to cope with cancer risk (91%), but 40% report anxiety/depression and worries cancer-specific. 65% has suffered stressful live events in the last 3 years. 28% have received psychological treatment in the last two years. The scores on Anxiety-Trait (STAI-R) were on normal range for Spanish population. MANOVA gender x hereditary syndromes (breast/ovarian, colon and others) showed higher scores of colorectal cancer participants on STAI-R (p=0.009); Moreover, women with previous cancer have a higher score on STAI-R than women without previous cancer diagnostic. There were 33 (25%) of 133 participants assessed that need psychological attention. AMOS 5 regression model with observed variables: STAI-R, previous cancer diagnostic, risk perception, number of cancer relatives, and stressful life events, explained 51% of the variance of psychological treatment needs. The analysis of ROC Curve using as contrast STAI-T variable to classify participants as positive or negative for need of psychological treatment showed that the STAI-R is a useful screening tool for psychological treatment needs. It is concluded that psychological intervention is necessary for a significative number of CGO participants.